THE LENGTH OF FREE RUN AND RELATIVE NUMBER OF RUNWAY ELECTRONS IN NONIDEAL PLASMA. - Ramazanov, T. S.; Turekhanova, K. M. (Recent Contributions to Physics, 2009)
In this work the effect of electron runaway is investigated for nonideal plasma. The dependences of free run length of electrons on plasma density and nonideality parameters are obtained. The relative number of runaway electrons on their velocity or temperature is considered for classical and semiclassical models of nonideal plasma.